Omental graft use in Youssef syndrome - Sapmaz, E; Celik, H; Semerciöz, A (Elsevier Sci Ireland Ltd, 2003)
Objective: To investigate the use of omental graft following the repair of fistula between bladder and uterus (Youssef syndrome). Methods: Primary repair was performed on four women who had developed vesico-uterine/vesico-cervical fistula and infertility due to previous low segment caeserean between October 1997 and January 2001. An omental graft of 4 cm x 3.5 cm was placed between bladder and uterus. Results: Repair was successful in all four patients. Complaints of amenorrhea, menouria and in three patients urine-type vaginal flux disappeared. Three patients did not want pregnancy, so contraceptives were administered. The fourth patient conceived after 4 months. Conclusions: This operation is both simple and effective. Fertility is recovered quickly. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: hysterosalpingography; omental graft; vesico-uterine/vesico-cervical fistula; Youssef syndrome